2022
DOI: 10.3390/bioengineering9040168
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineering Strategies to Create 3D Cardiac Constructs from Human Induced Pluripotent Stem Cells

Abstract: Human induced pluripotent stem cells (hiPSCs) can be used to generate various cell types in the human body. Hence, hiPSC-derived cardiomyocytes (hiPSC-CMs) represent a significant cell source for disease modeling, drug testing, and regenerative medicine. The immaturity of hiPSC-CMs in two-dimensional (2D) culture limit their applications. Cardiac tissue engineering provides a new promise for both basic and clinical research. Advanced bioengineered cardiac in vitro models can create contractile structures that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 187 publications
0
8
0
Order By: Relevance
“…In addition to growing longer, the increasing trend in organization index indicates the sarcomeres also become more organized during maturation in the 3D environment with laminin-521. Other groups have also observed an increase in sarcomere organization of iPSC-CMs cultured in ECM ( 35 ).…”
Section: Discussionmentioning
confidence: 89%
“…In addition to growing longer, the increasing trend in organization index indicates the sarcomeres also become more organized during maturation in the 3D environment with laminin-521. Other groups have also observed an increase in sarcomere organization of iPSC-CMs cultured in ECM ( 35 ).…”
Section: Discussionmentioning
confidence: 89%
“…Microactuators can give either electrical or mechanical stimuli to the cells/tissue, while the sensors record electrophysiological signals or contraction force [61]. Heart-on-a-chip has been used for drug toxicity assessments and maturation was shown to be improved through electrical and mechanical stimulation [62]. Although some cardiac disease models such as ischaemia and fibrosis have been investigated using the heart-on-a-chip method [63,64], to date there are no publications on its use for inherited cardiac arrhythmias.…”
Section: Heart-on-a-chipmentioning
confidence: 99%
“…These mutations are known to lead to familial arrhythmogenic cardiomyopathy with a high penetrance; however, there is a phenotypic variability in terms of disease onset, severity, and rate of progression. Recent evidence has shown that induced pluripotent stem cell (iPSC) represent a reliable strategy to create disease-in-a-dish models (Varzideh et al, 2022). Thus, the authors generated seven patient-specific iPSC lines with different LMNA mutations and successfully differentiated them in cardiomyocytes and cardiac fibroblasts.…”
Section: Editorial On the Research Topic Transcription Factors And Ar...mentioning
confidence: 99%